Virtual Reality Therapy (VRT) Intervention in Guidance and Counseling Services to Create Violence-Free Schools - Eka Aryani; Salleh Amat; Putri Taqwa Prasetyaningrum; Abdul Hadi; Anifa Tuzzuhroh Nurbaiti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
School violence, such as bullying and intimidation, remains a crucial issue with a serious impact on student well-being, despite various preventative measures. Conventional guidance and counseling services, which often employ methods such as lectures and group discussions, are considered ineffective in fostering empathy and providing a deeper understanding of the impact of violence. To address this gap, an innovative intervention called Virtual Reality Therapy (VRT) was proposed and implemented. VRT uses realistic simulations, allowing students to experience violent scenarios from multiple perspectives: as victims, perpetrators, and witnesses. The program includes training for guidance and counseling teachers, VR content creation workshops, and implementation support, aimed at improving their technical skills and readiness to adopt the technology. Evaluations using pretests and posttests showed significant improvement. This improvement demonstrates that VRT is an effective and transformative tool for creating safer and more violence-free school environments.